2019
DOI: 10.1007/s11064-019-02832-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Signalling Induces Casein Kinase 1-Dependent Formation of Cytosolic TDP-43 Inclusions in Motor Neuron-Like Cells

Abstract: Motor neuron disease (MND) is a progressive neurodegenerative disease with no effective treatment. One of the principal pathological hallmarks is the deposition of TAR DNA binding protein 43 (TDP-43) in cytoplasmic inclusions. TDP-43 aggregation occurs in both familial and sporadic MND; however, the mechanism of endogenous TDP-43 aggregation in disease is incompletely understood. This study focused on the induction of cytoplasmic accumulation of endogenous TDP-43 in the motor neuronal cell line NSC-34. The end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 77 publications
(103 reference statements)
0
22
0
Order By: Relevance
“…CK-1 was the first kinase identified to phosphorylate TDP-43 in vivo in more than 29 different sites, being 18 of them located in the C-terminal glycine-rich region 7 . Moreover, different stress signaling cause CK-1-dependent phosphorylation of TDP-43 triggering its cytosolic mislocalization and accumulation 8,9 . Furthermore, TDP-43 binds directly to and regulates the expression of CK-1ε mRNA 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CK-1 was the first kinase identified to phosphorylate TDP-43 in vivo in more than 29 different sites, being 18 of them located in the C-terminal glycine-rich region 7 . Moreover, different stress signaling cause CK-1-dependent phosphorylation of TDP-43 triggering its cytosolic mislocalization and accumulation 8,9 . Furthermore, TDP-43 binds directly to and regulates the expression of CK-1ε mRNA 10 .…”
mentioning
confidence: 99%
“…However, its dysregulation leads to different pathologies including cancer and neurodegenerative diseases 11 . Recently, inhibition of CK-1, mainly the δ and ε isoforms, has been proposed as a potential treatment for different neurodegenerative diseases including ALS, FTD 9 and Alzheimer's disease 12 .…”
mentioning
confidence: 99%
“…They reduced levels of nuclear TDP-43, decreased neuronal loss, and reversed cognitive and motor decline (Wenqiang et al, 2014). In subsequent studies, these TKIs could reverse the effects of TDP-43 on synaptic proteins, increase astrocytic function, and restore glutamate and neurotransmitter balance in TDP-43 transgenic mice that overexpressed the full length protein in neurons (Heyburn et al, 2016). Finally, in a recent high-throughput screening approach, bosutinib was found effective in iPSC-derived ALS patient cells (Imamura et al, 2017).…”
Section: F I G U R Ementioning
confidence: 98%
“…Notably, these inclusions did not occur following exposure to staurosporine as previously described in other systems (see above) or with trans‐4‐carboxy‐ l ‐proline (PDC). Recently, it has been reported that tunicamycin can induce CK1 expression in mature NSC‐34 cells that phosphorylates TDP‐43 and induces its translocation to the cytoplasm (Hicks, Cross, Williamson, & Rattray, 2020).…”
Section: Tdp‐43 Aggregate Formationmentioning
confidence: 99%
“…Researches showed that the decreased AQPs protein levels were correlated with ER stress [21]. Excessive ER stress could result in tissue damage and cell injury, and it has been observed in many inflammatory diseases, including asthma [22,23]. Recent studies indicate that ER stress might be a potential target for controlling inflammatory responses [24].…”
Section: Introductionmentioning
confidence: 99%